Identification of 5-hydroxytryptamine receptor gene polymorphisms modulating hyperprolactinaemia in antipsychotic drug-treated patients with schizophrenia; The World Journal of Biological Psychiatry; Vol. 18, iss. 3 - Ivanova S. A. Svetlana Aleksandrovna; Osmanova D. Z. Diana; Freydin M. V.; Fedorenko O. Yu. Olga Yurievna; Boyko A. S. Anastasiya Sergeevna; Pozhidaev I. V. Ivan; Semke A. V. Arkady Valentinovich; Bokhan N. A. Nikolay Aleksandrovich; Agarkov A. A. Aleksey Aleksandrovich; Vilffert B. Bob; Loonen A. J. M. Anton (2016, 2016)
Title screen